Development of a reference rubric (R2) to promote the use of rubrics in higher education, and comparison of the rubric of each subject with the R2 - Nakata, Yasuo; Kozaki, Ryosuke; Murakami, Katsuhiko; Itoh, Akira; Takamatsu, Kunihiko; Omori, Masato; Kirimura, Takafumi; Mitsunari, Kenichirou; Kondo, Mizuki; Kitamatsu, Ryohei; Nishiyama, Keita; Bannaka, Kenya; et al. (Journal of Learning Analytics, 2024)
Implementing rubrics in the syllabus in Japanese higher education is difficult. Syllabus creation is widespread enough, but rubric-based syllabi are slow to spread. Kobe Tokiwa University first created a reference rubric (R2) and presented it as a model. Subsequently, a rubric-based syllabus was formulated for one grade at a time each year. After introducing the reference mentioned above rubric, we organized ‘Significant Other Groups (SOGRs)’ consisting of students, staff, faculty, alumni, and third parties. In order to determine how the faculty members adapted to create a rubric-based syllabus, we propose a method for examining the similarity between the reference rubric (R2) and the subject rubric using machine learning-based similarity calculations based on the evidence-based evaluation by Eduinformatics.